Peran Bendahara Pengeluaran dalam Meningkatkan Akuntabilitas Keuangan Melalui Sistem Aplikasi Keuangan Pada Pengadilan Negeri Bangil - Sonya MD Siregar (Jaanur Elbarik Indonesia, 2025)
This study aims to determine the role of the expenditure treasurer in improving financial accountability in Bangil District Court. Using a descriptive qualitative approach, data was collected through in-depth interviews, direct observation, and document analysis. The results showed that the expenditure treasurer has a strategic responsibility in managing the entire budget cycle, from planning, implementation, to reporting. The use of government financial applications such as SAKTI supports efficiency and accuracy in financial reporting, although its success depends heavily on the competence and integrity of human resources. In addition, regular internal monitoring also contributes to maintaining accountability. However, challenges such as limited technical training and lack of leadership support remain. This study concludes that expenditure treasurers play a central role in ensuring financial transparency and accountability in judicial institutions.